ASSESSMENT OF MAXILLOFACIAL TRAUMA IN KANJURUHAN GENERAL HOSPITAL MALANG USING FACIAL INJURY SEVERITY SCALE (FISS) SCORING SYSTEM - Makayasa Putri, Kunthi Kencana; Deddy Setyo Nugroho (Jurnal Rekonstruksi dan Estetik, 2025)
Highlights:  Most maxillofacial trauma cases were mild, based on FISS scoring. The average FISS score was 3.37, with most patients scoring 2 (24.7%). Larger studies are needed to confirm FISS as a prognostic tool. Abstract: Introduction: Maxillofacial trauma is a unique form of trauma that may lead to various facial function disabilities. One method to assess the severity of maxillofacial fractures is the Facial Injury Severity Scale (FISS). This study aims to describe and evaluate the severity of maxillofacial trauma cases in the Emergency Room of Kanjuruhan General Hospital Malang using the FISS scoring system, from January 2022 to December 2023. Methods: This retrospective study collected data from patients with maxillofacial trauma treated at the Emergency Room of Kanjuruhan General Hospital Malang between January 2022 and December 2023. The variables recorded included age, gender, etiology, helmet use, type of fracture, and treatment received. Each patient was evaluated using the FISS scoring system to determine the severity level. Results: A total of 73 subjects were included. The youngest patient was 2 years old, and the oldest was 76 years. The average FISS score was 3.37 ± 1.9, with scores ranging from 1 to 9. Most patients had a FISS score of 2 (24.7%). Conclusion: The majority of maxillofacial trauma cases in the Emergency Room of Kanjuruhan General Hospital were classified as mild according to the FISS scoring system. Further studies with a larger sample size and a complete maxillofacial trauma database are needed to evaluate the prognostic value of the FISS system.